Food insecurity on a college campus: Prevalence, determinants, and solutions. Issue 1 (14th February 2022) - Adamovic, Emilie; Newton, Peter; House, Veronica
Abstract: Objective: Students are at risk of food insecurity. We aimed to determine: the prevalence of food insecurity among students; the variables associated with student food insecurity; and appropriate solutions. Participants: We collected data from 339 students at a large state university in the western United States between December 2016 and February 2017. Methods: We used an anonymous online survey that incorporated the USDA US Six-Item Short Food Security Survey. Results: First, 54% of respondents had been food insecure within the last year. Second, students in receipt of financial aid were significantly more likely to be food insecure. Third, respondents proposed solutions to student food insecurity that included on-campus food assistance programs, education initiatives, and off-campus food assistance programs. Conclusions: Our paper contributes to a growing body of knowledge about the extent and causes of, and solutions to, food insecurity among college students.